Mulberry-like heterostructure (Fe–O–Ti): a novel sensing material for ethanol gas sensors. Issue 16 (19th March 2019) - Li, Min; Shen, Jianxing; Cheng, Chuanbing; Wang, Tailin; Shen, Yan; Wang, Shuai; Chen, Pan
Abstract : The gas sensors have been widely used in various fields, to protect the safety of life and property. Abstract : The gas sensors have been widely used in various fields, to protect the safety of life and property. A novel heterostructure of Fe–O–Ti nanoparticles is fabricated by hydrothermal and wet chemical deposition methods. The Fe–O–Ti nanoparticles with a large number of pores possess high surface area, which is in favour of high-performance gas sensors. Compared with pure Fe2 O3 and TiO2, the Fe–O–Ti composite exhibits obviously enhanced sensing characteristics, such as faster response–recovery time ( T res = 6 s, T rec = 48 s), higher sensing response (response = 35.6) and better selectivity. The results show that the special morphology and large specific surface area of mulberry-like Fe–O–Ti heterostructures provided a large contact area for gas reactions.